Biting palsy of the accessory nerve. - Paljärvi, L (1980)
A young man was bitten by his girl friend at the anterior border of the left trapezius muscle. Weakness of the trapezius resulted and a longstanding ache in the shoulder developed. Clinically and neurophysiologically, an axonotmesis type crush injury of the accessory nerve was verified.